'We're Just the Gravel on the Road.' The Dissenting Music of Tom Waits. (3rd July 2021) - Tedde, Adriano
ABSTRACT: This article proposes a historicisation of the songs of Tom Waits in the context of the social transformation of the United States in the era of neoliberalism. Through an analysis of music and lyrics – form and content, the article explores questions of poverty, materialism, social injustice, and other issues referable to the impact of neoliberal politics on everyday America. Those issues are particularly evident in the songs composed by the singer-songwriter with his wife and artistic partner, Kathleen Brennan, since the mid-1980s. Using a Rortyan framework, this study finds a place for the music of Tom Waits in the American protest song, arguing that it mirrors the fall of American society into extreme individualism and materialism, while celebrating the solidarity and human warmth of a utopian social hope.